UNODA Occasional Papers No.26: The New Zealand Lectures on Disarmament by High Representative Angela Kane, June 2014 - United Nations (United Nations, 2014)
The United Nations Office for Disarmament Affairs (UNODA) Occasional Papers is a series of ad hoc publications presenting, in edited form, papers or statements made at meetings, symposiums, seminars, workshops or lectures that deal with topical issues in the field of arms limitation, disarmament and international security. They are intended primarily for those concerned with these matters in Government, civil society and in the academic community. This Occasional Paper is a collection of High Representative Angela Kane's speeches during her visit to New Zealand in April 2014. The speeches she delivered at a range of venues provide a comprehensive stocktake of the prospects and challenges currently confronting disarmament and arms control efforts. Her balance sheet registers both progress, most notably in the field of conventional arms (in particular, last year’s historic adoption of the Arms Trade Treaty), and a lack of progress—especially as regards nuclear disarmament.